Ovarian stimulation for fertility preservation in a woman with borderline serous ovarian tumor causing a large fluctuating subcutaneous fluid collection: a case report - Ranit Hizkiyahu; Shannon Salvador; Michael H. Dahan (IMR Press, 2021)
Background: Fertility preservation in oncologic cases has increased exponentially during the last 15 years. Most of these cases occur in women with breast cancer or lymphoma. Rarely, the onco-fertility physician will have cases of young ovarian cancer patients who wish to cryopreserve their oocytes or embryos. Case: A previously un-described presentation of a borderline serous ovarian tumor in a woman undergoing ovarian stimulation for fertility preservation. On the day of egg retrieval, a large subcutaneous fluid collection was noted. This fluid collection is possibly secondary to laparoscopic resection of the ovarian mass. Although, cancer recurrence has been noted at laparoscopic port entry sites and ovarian stimulation has been hypothesized to increase the risk of advancement of ovarian cancer cells, this is the first time in the medical literature that a supra-facial fluid collection occurred during gonadotropin stimulation, without ovarian hyperstimulation syndrome, in the context of ovarian malignancy. Our hypothesis is that during an operation before the stimulation cycle started, low malignant potential ovarian cells spread via the laparoscopy port to the subcutaneous space and grew in response to the gonadotropin stimulation. Conclusions: Being a borderline tumor, the fluid collection was self limited and did not re-occur with subsequent stimulations. However, in cases of frank ovarian malignacy and ovarian stimulation for fertility preservation cancer metastacis could occur to the sub-cutaneous space.